2016
DOI: 10.1111/and.12690
|View full text |Cite
|
Sign up to set email alerts
|

The presence of seminal plasma, especially derived from stallion semen, helps preserve chilled Asian elephant (Elephas maximus) sperm motility

Abstract: The effects of seminal plasma (SP), derived from autologous, homologous and heterologous species (stallion, boar and dog) on chilled Asian elephant sperm quality, were determined. Semen was collected from eight males and samples with ≥30% motile spermatozoa were used in the study. Semen was diluted with Tris-glucose-egg yolk extender, supplemented with different SP types and preserved at 4°C for 48 hr. Experiment 1 (n = 31), showed that the presence of SP (autologous) helped to preserve sperm quality in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Restoring SP proportion with stallion (heterologous) SP gave better results for sperm motility and velocities than those of un‐restored and elephant SP restored samples. The beneficial effect of stallion SP on chilled elephant sperm has been previously reported (Pinyopummin et al., ). In this study, it was further demonstrated that there was a beneficial effect in highly diluted samples, which could be useful for an elephant AI procedure, in which a large volume of semen might be required for deposition in the female reproductive tract (Brown et al., ; Thongtip et al., ).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Restoring SP proportion with stallion (heterologous) SP gave better results for sperm motility and velocities than those of un‐restored and elephant SP restored samples. The beneficial effect of stallion SP on chilled elephant sperm has been previously reported (Pinyopummin et al., ). In this study, it was further demonstrated that there was a beneficial effect in highly diluted samples, which could be useful for an elephant AI procedure, in which a large volume of semen might be required for deposition in the female reproductive tract (Brown et al., ; Thongtip et al., ).…”
Section: Discussionmentioning
confidence: 64%
“…The component in stallion SP that supported elephant sperm motility was not identified. However, SP proteins might respond for this effect as previously discussed (Pinyopummin et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, seminal plasma derived from stallions can maintain the sperm motility of Asian elephants during the cooling process (Pinyopummin et al, 2017).…”
Section: Seminal Plasmamentioning
confidence: 99%